2019
DOI: 10.1039/c9cc01026b
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-slaved protein motions accompany proton coupled electron transfer reactions catalysed by copper nitrite reductase

Abstract: A novel approach to study PCET reactions illustrates the importance of solvent-slaved protein motions in copper nitrite reductase catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
6
14
0
Order By: Relevance
“…This long hydrogen bond and the indirect connection between WatA and WatB indicate that PT from bulk water needs thermodynamic fluctuations to rearrange hydrogen bond networks. This is consistent with that protein flexibility coupled with solvent motions controls proton transfer, which precedes the ET reaction in CuNIR (50). A slightly low occupancy of Wat2 implies its flexibility, which may be important to bring proton to the T2Cu site via Asp CAT .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This long hydrogen bond and the indirect connection between WatA and WatB indicate that PT from bulk water needs thermodynamic fluctuations to rearrange hydrogen bond networks. This is consistent with that protein flexibility coupled with solvent motions controls proton transfer, which precedes the ET reaction in CuNIR (50). A slightly low occupancy of Wat2 implies its flexibility, which may be important to bring proton to the T2Cu site via Asp CAT .…”
Section: Resultssupporting
confidence: 84%
“…The O γ atom of Thr137 was a hydrogen donor to Asp112, the entrance residue of the MPC, and a hydrogen acceptor from the O γ atom of Ser96 that is a hydrogen acceptor from the amide moiety of Gly136. The observed hydrogen bond network shows the connection between the T1Cu site and the MPC, which may be involved in PCET accelerated by solvent-slaved protein motions (50).…”
Section: Resultsmentioning
confidence: 92%
“…Our examinations revealed that the driving force of intra‐ET comes from the remote water‐mediated triple‐proton transfer along the both proton channels. These results are consistent with the recent proposal of PT along the long water hydrogen bond network coupled ET in CuNiRs by experimental methods [64,65] . In general, the special PT/ET reactions further confirm the diversity of biological proton‐coupled ET mechanisms [66–71] …”
Section: Resultssupporting
confidence: 90%
“…These results are consistent with the recent proposal of PT along the long water hydrogen bond network coupled ET in CuNiRs by experimental methods. [64,65] In general, the special PT/ET reactions further confirm the diversity of biological proton-coupled ET mechanisms. [66][67][68][69][70][71]…”
Section: Long-range Pt Along the Primary Proton Channelmentioning
confidence: 63%
“…analysis. EPR measurements were carried out using a Bruker ELEXSYS-500/580 Xband EPR spectrometer operating in both continuous-wave (cw) and pulsed modes, equipped with an Oxford variabletemperature unit and ESR900 cryostat with Super High-Q resonator as reported previously (63)(64). All EPR samples were prepared in the quartz capillary tubes (outer diameter; 4.0 mm, inner diameter 3.0 mm) and flash-frozen immediately and stored in liquid N2 until analysis.…”
Section: Electron Paramagnetic Resonance (Epr)mentioning
confidence: 99%